Persepsi Mahasiswa Sosiologi Agama Universitas Islam Negeri Sumatera Utara terhadap Victim Blaming pada Kekerasan Seksual di Perguruan Tinggi Indonesia - Nurhalimah Nurhalimah; Neila Susanti; Muhammad Jailani (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to describe the perceptions of Sociology of Religion college students at the State Islamic University of North Sumatra towards victims of sexual violence at Indonesian universities. In general, perception is a person's way of looking at something. This research uses a quantitative descriptive type and approach. The population of this study was 281 Sociology of Religion college students at the State Islamic University of North Sumatra, with a margin of error of 10%, and a sample of 74 people. The sampling technique used is stratified random sampling. Questionnaires are a data collection technique with a perception measuring tool in the form of a Likert scale. The results of the research reveal that the perception of Sociology of Religion college students at the North Sumatra State Islamic University towards victims blaming for sexual violence in Indonesian universities is negative. Respondents are know victim blaming well, victim blaming is often found in cases of sexual violence, where women are the ones who are vulnerable to becoming objects of sexual violence. This is characterized by siding with victims of sexual violence, such as sympathy and empathy for victims, victims must receive protection, victims of violence do not deserve to be blamed, and justifying incidents of sexual violence as not being caused by the victim's behavior. Meanwhile, other neutral responses revealed that the way women dress and their body shape are the causes of sexual violence. This means that women who wear closed or open clothing both have the opportunity to become victims. Furthermore, neutral responses to victims of sexual violence always exaggerate the cases at hand. On the contrary, the news media tends to exaggerate so that it leads to opinion, which ends up making it difficult for the victim to reveal the case they are facing because of concerns about giving the victim a negative stigma.